Randomized controlled pilot study of an app-based intervention for improving social skills, face perception, and eye gaze among youth with autism spectrum disorder - Chung, Kyongmee; Chung, Eunsun (Frontiers in Psychiatry, 2023)
children with autism spectrum disorder. Yface is a combined program that improves social skills, facial perception, and eye gaze. Children were randomly assigned to one of the two training groups or a waitlist control group. One of the training groups completed the Yface training program lasting for 66 days, while the other training group used a similar app called Ycog, which focuses on cognitive rehabilitation. Questionnaires, computerized tasks, and semi-structured interviews were administered to children and their parents at pre- and post-training sessions. The Yface group showed improvements in face perception and some social skills compared to waitlist controls, and in eye gaze compared to the Ycog group. Our results suggest that this app-based intervention is effective in improving targeted social skills and face perception, although their relative effectiveness differs across skill domains.